STRENGTHENING EMPLOYEE PERFORMANCE THROUGH THE SYNERGY OF LEARNING AGILITY AND WORK ENVIRONMENT WITH DIGITAL COMPETENCE AS A MEDIATING VARIABLE IN THE PUBLIC SECTOR - Afri Dian Setiyani; Yudi Nur Supriadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the influence of learning agility and work environment on employee performance with digital competence as a mediating variable, among employees of the National Public Procurement Agency (LKPP). This research is motivated by the importance of adaptive capabilities and mastery of digital technology in supporting employee performance in the era of digital transformation. The research method uses a quantitative approach with Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis technique. The sample for this study consisted of 102 employees at the National Public Procurement Agency, selected through random sampling. The research instrument used a Likert scale questionnaire with four main variables. The results show that learning agility has a significant influence on digital competence and employee performance. Although digital competence does not have a direct significant influence on performance, this variable acts as a partial mediator. Meanwhile, the work environment does not show a significant influence on either digital competence or employee performance. These findings provide important implications for public sector employee development efforts focused on increasing agility and digital literacy to support the success of digital transformation.